Analisis peramalan kebutuhan raw material di perusahaan pakan ternak dengan menggunakan metode time series - Maida, Salsabilla Nur; Dewi, Sinta (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT XYZ is a company engaged in the animal feed industry that implements the Make To Order (MTO) system. Raw materials Rice Brand (Katul), Soya Bean Meal (SBM), and Crude Palm Oil (CPO) are raw materials that are often used in animal feed production. Because the uncertain demand for feed causes problems in predicting the amount of raw material stock. The purpose of this study is to compare three forecasting methods based on the historical data patterns of each raw material. There are three methods used, namely Single Exponential Smoothing, Moving Average, and Weighted Moving Average. After the data error test was carried out, it was found that the Weighted Moving Average method had the smallest error value for each raw material, namely with the forecast on Rice Brand (Katul) which is 102,241 tons with a MAPE value of 0.44334; Soya Bean Meal (SBM) 787,090 tons with a MAPE value of 0.0858; and Crude Palm Oil (CPO) which is 86,072 tons with a MAPE value of 0.1465.